Grave Risk and the Right to Return: A Comparative Study of Judicial Responses to International Child Abduction - Hermansyah (Legalis : Journal of Law Review, 2025)
This article analyzes the application of the grave risk exception under Article 13(1)(b) of the 1980 Hague Convention on the Civil Aspects of International Child Abduction, comparing approaches in the United States, the European Union, and the Hague Conference on Private International Law (HCCH). With international child abduction cases increasing by about 35% over the past two decades (HCCH, 2021), courts face growing tension between ensuring the prompt return of children and safeguarding their welfare. The study employs a comparative doctrinal and case study methodology, examining legal texts, jurisprudence, and soft-law instruments such as the HCCH Guide to Good Practice, complemented by empirical data from the HCCH Statistical Study (2021) and regional reports. Findings reveal marked divergence across jurisdictions. U.S. courts apply a high evidentiary threshold and defer to trial-level findings, prioritizing return obligations. EU courts, guided by Brussels II bis, integrate structured timelines and protective measures to mitigate potential harm. The HCCH, through soft-law harmonization, encourages consistent interpretation, though implementation remains uneven. Protective tools—such as mirror orders and supervised contact—are most effective when supported by enforceable judicial mechanisms. The article concludes that achieving consistency in grave risk assessments requires legal harmonization, judicial education, and stronger cross-border enforcement frameworks. Policy recommendations include standardized evaluation protocols, enhanced training for judges, and international cooperation to align legal practices with the child’s best interests.